Structure and Biosynthesis of Fimsbactins A–F, Siderophores from Acinetobacter baumannii and Acinetobacter baylyi. Issue 5 (1st March 2013) - Proschak, Anna; Lubuta, Patrice; Grün, Peter; Löhr, Frank; Wilharm, Gottfried; De Berardinis, Veronique; Bode, Helge B.
Abstract Novel chatechol/hydroxamate siderophores (named "fimsbactins") were identified in Acinetobacter baumannii ATCC 17978 and Acinetobacter baylyi ADP1. The major compound, fimsbactin A, was isolated from low‐iron cultures of A. baylyi ADP1, and its chemical structure was elucidated by mass spectrometry, and detailed 1H, 13C and 15N NMR spectroscopy. From inverse feeding experiments following HPLC‐MS analysis, the structures of five additional derivatives were elucidated. The gene cluster encoding the fimsbactin synthetase (fbs) was identified in both genomes, and mutants in fbs genes in A. baylyi were analyzed, thus allowing prediction of the fimsbactin biosynthesis pathway.